CATALYTIC REFORMING OF PURE HYDROCARBONS AND NAPHTHA USING MONO AND BI-METALLIC REFORMING CATALYSTS - A.S. Nasution (Scientific Contributions Oil and Gas, 1988)
The catalytic role of mono and bi-metallic of reforming catalysts is studied for the conversion of pure hydrocarbons: Le n, hexane, n. heptane, n, octane, methylcyclopentanÄ™, cyclohexane and nephtha in the reformning reaction